GLOSARIUM FAUNA HASIL LAUT DALAM BAHASA MELAYU SUKADANA - Vellia, Tengku Lisa; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research is to describe all the vocabulary of marine of fish and non-fish in the Malay language of Sukadana. The methods used are qualitative and quantitative. The data of the research is a Sukadana Malay language which is spoken by the informant in the village of Sutera, Sukadana subdistrict, North Kayong regency. The techniques of data collection are fishing techniques, proficient techniques, capable of tansemuka capable techniques, recording and record techniques. Based on the overall vocabulary data of marine fauna classification consists of a fish of 79 vocabulary and non-fish as many as 13 vocabulary. The fauna of the sea's vocabulary as a whole has a lexical meaning of 67 and a cultural significance of 92 vocabulary. This research relates to the Curriculum 2013 on Indonesian subjects in the first semester of grade seven in SMP which suggested to be a reference for contextual text material for teaching and learning process. This research can be applied in social practice which includes biological, sociological, and ideological dimensions between interrelated to languages.Â Keywords: Fish and Nonâ€“fish, Malay Society in Sukadana, The Vocabulary of Marine Fauna